Slider‐based multi‐objective control for resilient microgrids - Kevin P. Schneider; Francis K. Tuffner; Yingying Tang; Nikitha Radhakrishnan; Priya Thekkumparambath; Wei Du; Jayant Kumar; Subrahmanyam S. Venkata (IET Generation, Transmission & Distribution, 2020)
The desire to modernise electrical infrastructure, and the increasing number of extreme weather events, has led to an increased interest in deploying microgrids as resiliency resources. While there are times when a microgrid is operated to increase the resiliency of critical end‐use loads, there are also other operational goals, such as efficiency, that may be considered. However, it can be challenging for microgrid operators to coordinate assets in real time to balance operational objectives. This study presents a slider‐based multi‐objective control that enables microgrid operators to change the operational set points of microgrid assets to respond to rapidly changing system conditions.